Ground Water Level as an Indicator of Fire in Tanjung Jabung Timur, Jambi Province - Putri, Atfi Indriany; Syaufina, Lailan; Puspaningsih, Nining (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Forest and land fires become one of the environmental issues every year, that are discussed by the community, both at local, national, and international levels. Factors that affect fires on peatlands include water level, hotspots, and rainfall. Peatland and Mangrove Restoration Agency for the past few years have made a tool in the form of a Peatland Water Monitoring System (SIPALAGA) sensor with the aim of measuring water level. The purpose of this study is to (1) analyze the relationship between water level and hotspots as an indicator of forest and land fires, and (2) analyze water level with rainfall. Tanjung Jabung Timur Regency has a hotspot distribution for the period January 2019 – December 2021 worth 916 hotspots. The results of the correlation test of the hotspot relationship with water level obtained a moderate correlation value with a value of -0.408 and P-Value of 0.001, it shows that hotspots with high water levels have a negative relationship, which means that high hotspot values ​​will be followed together with a decrease in high values. water face. As for the correlation of water level with rainfall, it gets a high correlation value with a value of 0.705 with a P-Value of 0.001 and has a positive notation, which means that a high amount of rainfall will be followed by a high water level value.